Comparison between manual and mechanical chest compressions during resuscitation in a pediatric animal model of asphyxial cardiac arrest - López, Jorge; Fernández, Sarah N.; González, Rafael; Solana, María J.; Urbano, Javier; Toledo, Blanca; López-Herce, Jesús (PLOS ONE, 2017)
Aims Chest compressions (CC) during cardiopulmonary resuscitation are not sufficiently effective in many circumstances. Mechanical CC could be more effective than manual CC, but there are no studies comparing both techniques in children. The objective of this study was to compare the effectiveness of manual and mechanical chest compressions with Thumper device in a pediatric cardiac arrest animal model. Material and methods An experimental model of asphyxial cardiac arrest (CA) in 50 piglets (mean weight 9.6 kg) was used. Animals were randomized to receive either manual CC or mechanical CC using a pediatric piston chest compressions device (Life-Stat®, Michigan Instruments). Mean arterial pressure (MAP), arterial blood gases and end-tidal CO2 (etCO2) values were measured at 3, 9, 18 and 24 minutes after the beginning of resuscitation. Results There were no significant differences in MAP, DAP, arterial blood gases and etCO2 between chest compression techniques during CPR. Survival rate was higher in the manual CC (15 of 30 = 50%) than in the mechanical CC group (3 of 20 = 15%) p = 0.016. In the mechanical CC group there was a non significant higher incidence of haemorrhage through the endotracheal tube (45% vs 20%, p = 0.114). Conclusions In a pediatric animal model of cardiac arrest, mechanical piston chest compressions produced lower survival rates than manual chest compressions, without any differences in hemodynamic and respiratory parameters.